The design, implementation and evaluation of an English language development component within a Grahamstown community project - Jefferay, Charlotte Ruth (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1994)
The Grahamstown Tertiary Education Bridging Project (GRATEP) was formed in 1991 by a group of post-matriculants from Grahamstown who had not been accepted into any tertiary institution for 1991. The overall aim of GRATEP was to prepare these students for tertiary education. The Academic Skills Programme at Rhodes University offered a programme in English Language Development. The present study aimed to research the design, implementation and evaluation of the GRATEP English Language Development programme which was implemented from May through to October 1991. A multimethod approach has been used to assess the progress made by the students in terms of developing communicative competence in English and to evaluate the course itself. The data included writing samples, questionnaires, exercises in hierarchical organization, a clozetest, comments made by the students and the participant observers. The programme appeared to have been most effective in terms of building confidence, developing academic skills and encouraging the students to take greater responsibility for their own learning. Statistical comparisons of the first and final writing samples revealed no overall significant improvement in communicative competence in English. However, comparisons of the scores in the categories and sub-categories of communicative competence revealed that students had improved in their ability to structure and organize their writing. The research raised questions about the design, implementation and assessment of non-formal language courses of this kind and made suggestions for improvement and further research.
Keywords: Grahamstown Tertiary Education Bridging Project; English language -- Study and teaching -- South Africa -- Foreign speakers; English language -- Writing -- Study and teaching -- South Africa -- Foreign speakers